Ecofeminist Kitchens: Reimagining Professional Kitchens as Spaces of Sustainable Foodwork - Adele Wylie (Feminismo/s)
Professional kitchens are both producers and consumers of food and many operate through unsustainable practices which have significant social and ecological impacts. Socially, they are spaces of low paid, high-pressured work, where gendered occupational discrimination is common. Ecologically, food production in these spaces contributes significantly to the demand for unethical meat production and the commodification of nature globally. The main aim of this article is to reimagine professional kitchens as spaces of sustainable and equitable foodwork. To this end, this research combines an empirical analysis of the relation between gender, power, and sustainability in professional kitchens in Glasgow with a theoretical examination of ecofeminist scholarship. In Glasgow, data were collected through semi-structured interviews with both male and female head chefs on the everyday (un)sustainable practices and norms of professional chefs and the ways they intertwine with gender. This research found that kitchens are organised in ways that normalize toxic masculinity, disempower women, and seriously harm non-human others. Furthermore, the absence of ecological literacy in professional kitchens is shown to be a significant driver of unsustainable behaviours. Drawing on ecofeminist scholarship, this article goes on to envision what changes are needed for a sustainable and equitable transformation in professional kitchens. Based on this theoretical engagement, I argue that transforming professional kitchens requires a redistribution of power across genders to eradicate sexist hierarchies. Furthermore, there is a need to decenter economic profit to make space for an ethic of compassion which fulfils our moral obligations to both human and non-human others.